Experimental Investigation on AISI 304l & AISI 310 Alloys Welded by Gas Metal Arc Welding (GMAW) Process - Singh, Sandeep; Kumar, Sanjeev; Singh, Harvant; Singh, Lovedeep (Asian Review of Mechanical Engineering, 2014)
In this research is to study the influence parameters affecting the mechanical property (microhardness) and optical investigation (microscopy) of austenitic stainless steel grade (AISI-304L& AISI-310) with Gas Metal Arc Welding (GMAW). The research was applying the different values of wire speed and current for experiment, which have following interested parameters: welding current at (180, 250 and 320 Amps), welding wire speeds at (2, 3, 5 m/min), shield gas pure CO₂ and (24V)Welding Voltage. The study was done in following aspects: microhardness and optical investigation. A research study investigate the maximum value of micro hardness for welding joint is 444.9 Hv at wire speed 3m/min and 250 Amps welding current. From the microscopy that HAZ has finer grain and interdendrictic austenitic phase at wire speed 3m/min & 250 Amps current which may cause the high tensile strength & micro hardness.